Belajar Strategi Pengembangan SQ Kepada Muhammad SAW - Abdul Wahid Hasan (Millah: Journal of Religious Studies, 2004)
The Spiritual Intelligence (SI) or Spiritual Quotient (SO) discourse has become an interesting study in the realm of  education and  psychology since Danah Zohar and Ian Marshall introduced SQ theory as the third intelligence, the ultimate intelligence and the necessary foundation for  the effective functioning of  both  IQ and EO. Ironically, the researchers of  SO coming from west who are non-Moslems have never mentioned Muhammad, as a man having high SO.  Whereas in  fact, his great, nobility and  spirituality have been  recognized by intelligentsia from both Moslems and non-Moslems. In other hand, he is the greatest educator to the humankind. This paper tries to place Muhammad  figure (pbuh) more objectively and wisely in the SQ discourse, and at the same time it explains how he teachs and educates his students so they become the renowned-world individuals leading the world and having high intelligence not only IQ and EQ but also SQ like AbuBakar, Umar, Ali etc.